(untitled) (International Seven Journal of Multidisciplinary, 2024)
Objective: To analyze the complications of obesity. Literature Review: Obesity is the global pandemic of the twenty-first century, it is a chronic pathology, characterized essentially by the accumulation of excess body fat. Research has shown that the situation is worrisome, since the consequences of obesity can directly interfere with the quality of life of the population, and according to Faeh D, et al. (2011) it is also associated with the growing mortality statistics. The increase in body fat is accompanied by profound changes in physiological functions, which can lead to adverse health effects, such as diabetes mellitus, cardiovascular diseases, dyslipidemias, chronic kidney disease, certain cancers, among other health problems. Final considerations: It is noteworthy that gastrointestinal and liver diseases, as well as their complications, become more accentuated with obesity, with a high prevalence of gastroesophageal reflux, erosive esophagitis, Barrett’s esophagus, erosive gastritis, dysbiosis, diarrhea, non-alcoholic fatty liver disease and even gastric cancer. Environmental, genetic, nutritional and immunological factors showed a strong relationship with the pathophysiological mechanisms involved in the development of these diseases.